Psychoanalysis and Literature: The Problem of the Discursive Subject - Sireikis, Augustas (Semiotika, 2025)
The article examines the concept of the discursive subject in psychoanalytic interpretation of literature. The relevance of the problem is grounded in two contradictory factors: (i) the tendency of classical psychoanalytic literary criticism to focus on the author or the reader as a substitute for the patient, and (ii) the formalist and structuralist assumption that discourse becomes a work of art only when it is enclosed and detached from empirical reality, including both the creator and the perceiver. This situation encourages testing the potential of the psychoanalytic perspective to account for this closure, which, according to Gérard Genette’s system of poetic theory, is associated with the fictionality of the text. For this purpose, the perspectives of three classics of psychoanalysis – Sigmund Freud, Melanie Klein and Jacques Lacan – are used to present three approaches to the same work – Giedra Radvilavičiūtė’s essay “Šiąnakt aš miegosiu prie sienos“ (literal translation: “Tonight I Will Sleep by the Wall”). The study concludes that Lacan’s concepts surpass the methodological tools of other theorists in that they enable and even encourage the separation of the discursive subject from the empirical author. And although this is based on a different concept of reality than the one that traditionally figures in studies of essays, documentary literature, and so-called autofiction, it calls for not a suspension, but a new way to raise and resolve the question of the boundary between fiction and reality.
Keywords: psychoanalysis; literature; subject; fiction; reality